China-Central Asia Cooperation for Regional Development: China Role on Kyrgyzstan’s Road to “Defragilization” - Santos, T. B. (State Building and Fragility Monitor, 2024)
In the past, China established cooperation with Central Asia with the main objective of safeguarding its border from cross-border terrorism. This was during a time when the Central Asian countries were initiating their process of state-building and were still very fragile. To achieve this, China recognised that promoting economic development in Central Asia and ensuring regional connectivity were crucial. Kyrgyzstan is one of the five Central Asian states and shares a border with China. It has been considered one of the most fragile states in the region due to its weak economy and lack of state legitimacy, and the presence of terrorist groups. In the last fifteen years, China has increased its investment in Kyrgyzstan to promote economic growth and assist in the state-building process, aiming for securitization. This paper aims to explore China's efforts towards “defragilization” in Kyrgyzstan and the potential future of cooperation between the two nations.